Awareness among the Dental students and Dental Interns of Kantipur Dental College and Hospital regarding Antibiotics Prophylaxis for Infective Endocarditis - Pokharel, Prenit Kumar; Chapagain, Shrijana (Journal of College of Medical Sciences-Nepal, 2019)
Background: Infective Endocarditis is relatively a rare disease and is believed to be caused by the vegetative growth on the previously damaged or congenitally malformed cardiac valves or endocardium. Several factors determines that the dentist practicing prophylaxis measures, the foremost important one is the knowledge which is taught to them during dental school, which is the main reason to conduct this study to test the awareness among the dental students of Kantipur Dental College and Hospital, Kathmandu regarding the prophylaxis guideline awareness. Methods: BDS Third, Fourth, Fifth year students and Dental Interns of Kantipur Dental College and Hospital were asked to fill the self-answered questionnaires. The questions were divided into two parts each part containing ten questions each. The first part was to access the knowledge of participants regarding the cardiac conditions that require antibiotics prophylaxis, the second part was to access the knowledge of participants regarding the dental procedures that requires antibiotics prophylaxis. Results: Thirty two percentage of our participants responded that forceps extraction does not require antibiotics prophylaxis which is not true as per AHA guideline, so the participants should be taught regarding the risk of forceps extraction leading to infective endocarditis if the prophylaxis is not administered. We postulated that majority of the Dental Students and Interns have heard about AHA 2007 guideline and will follow it when necessary. Conclusions: The participants who are the Dental Students and Dental Interns in a Dental School at Kathmandu, Nepal will be practicing Dentistry in near future, the knowledge they acquire during their learning period will help them to prevent the Infective endocarditis among the risk population whom they will be treating in near future. Measures should be taken to prevent the incidence of Infective Endocarditis with dental origin.